Constantin Bărbulescu, Physicians, peasants and modern medicine: Imagining rurality in Romania, 1860-1910, traduzione di Angela Jianu, Budapest, Central European University Press, 2019, pp. 308 - Eugenia Tognotti (Anuac, 2021)
Recensione di Constantin Bărbulescu, Physicians, peasants and modern medicine: Imagining rurality in Romania, 1860-1910, traduzione di Angela Jianu, Budapest, Central European University Press, 2019, pp. 308.